Relevansi Prinsip Pesantren Sami’na wa Atho’na dalam Filsafat Etika Immanuel Kant - Iklila, Difla; Fauzi, Ahmad (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This study examines the values embedded in the pesantren education system that form a patron-client relationship between kiai and santri. This relationship is characterized by the characteristics of imbalance, individuality, and breadth, which are reflected in pesantren educational literature such as Kitab Ta'lim Muta'allim. Qualitative methods will be used in writing this article, with qualitative methods integrating field research and literature studies to explore the relevance between the pesantren ethical principle of sami'na wa atho'na which means